The Timing of Option Repricing - Callaghan, Sandra Renfro; Saly, P. Jane; Subramaniam, Chandra (Journal of Finance, 2004)
ABSTRACT We investigate whether executive stock option repricings are systematically timed to coincide with favorable movements in the company's stock price. For a sample of 236 repricing events, we observe sharp increases in stock price in the 20‐day period following the repricing date. In addition, repricing dates tend to either precede the release of good news or follow the release of bad news in the quarterly earnings announcements. Since information about stock option repricing is not generally released to the public around the repricing date, these findings suggest that CEOs opportunistically manage the timing of the option repricing date.